ANALISIS LIKUIDITAS KOPERASI SIMPAN PINJAM KAMANGTAWAYA DESA SENDANGAN KECAMATAN REMBOKEN KABUPATEN MINAHASA - Monica P. Mumek; Theodora M. Katiandagho; Rine Kaunang; Charles R. Ngangi (Universitas Sam Ratulangi, 2014)
ABSTRACTThe objective of this study is to analyze the levels of liquidity Current Ratio of Credit Cooperative â€œKamangtawayaâ€, Sendangan Village Remboken Sub District Minahasa Regency, based on financial report from 2008 to 2013. Research was conducted at Cooperative â€œKamangtawayaâ€, Sendangan Village Remboken Sub District Minahasa Regency lasted for 4 months from January 2014 to April 2014. Data was collected by survey methods. Data collected was secondary data obtained from the data and the books of financial statements as well as interviewed with cooperative leader and treasurer. Data used from were data 2008 to 2013.The research result showed that Credit Cooperative â€œKamangtawayaâ€, Sendangan Village Remboken Sub District was good enough in managing their short-term liabilities, current ratio obtained by the cooperative is still in the normal phase that was is above 100%. So that the savings and Credit Cooperative Kamangtawaya still able to meet its short term obligations.